Augmented Reality (AR): Cybersecurity Risks in Military Applications - Gopal, Rajesh (Journal of Advanced Research in Electronics Engineering and Technology; Vol 12 No 1&2 (2025): Journal of Advanced Research in Electronics Engineering and Technology, 2025)
This research looks into cybersecurity pitfalls that come with using Augmented Reality (AR) in military settings, zeroing in on weaknesses adversaries might exploit. Drawing on a mix of qualitative data — from cybersecurity assessments in the military and chats with experts to case studies on AR systems in defence — it ends up uncovering some pretty critical security gaps and threat paths that seem unique to AR. The findings suggest that, while AR can offer a clear operational edge, it also brings along serious issues relating to data integrity, real-time navigational blips, and overall system hardiness when under attack. In most cases, there's a pressing need to put together strict cybersecurity measures that are designed specifically for AR platforms in such military environments. The broader importance of these insights stretches well beyond the battlefield, hinting at an urgent call for better cybersecurity practices across other defence-related tech and even in areas like healthcare, where AR is increasingly used for training simulations and patient care. At times, the results also point to the value of a closer working relationship between cyber specialists and military strategists, aiming to create robust frameworks that help shield key information systems from new threats. All in all, this study adds to the ongoing conversation about how technology and security intersect in military contexts, generally speaking, urging a more proactive approach in the face of rapid technological change.